Relasi Fungsi, Bentuk dan Material Pada Arsitektur Rumah Baja Karya Ahmad Djuhara - Danang Harito Wibowo (Jurnal Lingkungan Karya Arsitektur (LingKAr), 2022)
ABSTRACT Steel house by Ir. This Ahmad Djuhara I.A.I, comes with a prominent metal material dominance. In addition to being used in the main structure and the main outer enclosure, all these materials are displayed in a straightforward and naked manner. Making the expression of this building really unusual. Perhaps because of this, as far as is known, since 2002 it has received the most and widest coverage from the media (print, television and online) than any other architect's works. This steel house received an award from the Indonesian Architects Association (IAI Award), such as confirming the existence and presence of this unique steel house. This study aims to examine how the relationship aspects of Form, Function & Material. The method used is qualitative - descriptive. Through the study of the anatomy of the building, then data collection by means of field observations, direct interviews with users. Then, to fulfill its objectivity, interviews were also conducted on 15 residents (chosen randomly) who live around the location (radius not more than 600 m). The results of the study show that the relationship from triangulation aspects of Form, Function and Material does not work as expected, especially regarding materials. This research is expected to be useful for architectural science, practitioners and students. So that in its design, it is necessary to be more careful in determining the dominance of the material. Key word : Relation, Form, Function, Material, Building Anatomy and Steel house.